CircFGGY Inhibits Cell Growth, Invasion and Epithelial-Mesenchymal Transition of Hepatocellular Carcinoma via Regulating the miR-545-3p/Smad7 Axis - Feng, Kun-Liang; Diao, Na; Zhou, Zhai-Wen; Fang, Chong-Kai; Wang, Ji-Nan; Zhang, Ying; Luo, Rui; Zhong, Chong (Frontiers in Cell and Developmental Biology, 2022)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. Circular RNAs (circRNAs) play critical roles in the progression of HCC. However, the role of the newly identified circFGGY (hsa_circ_0006633) in the development and progression of HCC has not been explored. In this study, we found that circFGGY was significantly down-regulated in tumor compared with that in adjacent normal liver tissues of patients with HCC. HCC patients with low circFGGY expression had poor overall survival after hepatectomy. Moreover, it was found that circFGGY could inhibit the proliferation, invasion and epithelial-mesenchymal transition of HCC both in vivo and in vitro. Mechanistically, circFGGY promoted the expression of Smad7, a well-known suppressor of the transforming growth factor-β signaling pathway. In addition, miR-545-3p, a tumor promoter targeting both circFGGY and Smad7, suppressed the upregulation of Smad7 caused by circFGGY overexpression. Collectively, our data revealed that circFGGY inhibits the proliferation and invasion of HCC cells by sponging miR-545-3p and promote the expression of Smad7, indicating that circFGGY functions as a tumor suppressor and could be a prognostic biomarker for HCC.